Bojan - Gavran, Djuro (Croatia, 2010)
The documentary is about two friends Matija and Bojan who grew up together. Their friendship was suddenly interrupted when, overnight, Bojan and his family suddenly left their apartment, without even saying goodbye. Too young at the time to understand the war situation or why he lost his friend, fifteen years later, Matija decides to find his friend.
Verzio Film Festival Submission
Keywords: Documentary films